Analysis of the Influence of Customer Satisfaction on Mobile Banking Services at One of the State Owned Banks in Medan - Nasution, Ferdi Dermawan; Harahap, Rahmat Daim (LPPPIPublishing, 2024)
This research aims to determine the influence of mobile banking user-friendliness, mobile banking usage risks, and mobile banking service features on mobile banking services, both simultaneously and partially. The sample used in this study consisted of 30 participants. The research method employed a quantitative descriptive approach with multiple linear regression analysis techniques. The results of this study indicate that simultaneously, the variables of mobile banking user-friendliness and mobile banking service features have a positive and significant impact on customer satisfaction with mobile banking services. Partially, only the variable of mobile banking usage risks has a positive but nonsignificant influence on mobile banking services. The influence of service quality found in mobile banking is 58%, while 42% is influenced by other variables outside of this regression model.